2016
DOI: 10.1002/jgm.2876
|View full text |Cite
|
Sign up to set email alerts
|

Application of HIF‐1α by gene therapy enhances angiogenesis and osteogenesis in alveolar bone defect regeneration

Abstract: Overexpression of HIF-1α by gene therapy may be a useful method for enhancing alveolar bone defect osteogenesis and angiogenesis. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…Hypoxia is an important factor that induces ECs toward the formation of functional vasculature supporting blood supply [95,96]. The in vitro and in vivo effects of HIF-1α on osteogenesis and angiogenesis have been in-depth studied [97][98][99][100][101][102][103]. Wu et al [104] incorporated Cu within mesoporous bioactive glass (MBG) scaffolds with large pores (300-500 μm) and well-ordered mesopores (5 nm), and investigated the effects of Cu-induced hypoxia on hMSCs.…”
Section: Coppermentioning
confidence: 99%
“…Hypoxia is an important factor that induces ECs toward the formation of functional vasculature supporting blood supply [95,96]. The in vitro and in vivo effects of HIF-1α on osteogenesis and angiogenesis have been in-depth studied [97][98][99][100][101][102][103]. Wu et al [104] incorporated Cu within mesoporous bioactive glass (MBG) scaffolds with large pores (300-500 μm) and well-ordered mesopores (5 nm), and investigated the effects of Cu-induced hypoxia on hMSCs.…”
Section: Coppermentioning
confidence: 99%
“…A recent animal study reported new bone and vessel formation induced by the over-expression of HIF-1α through adenovirus, leading to enhanced alveolar bone defect regeneration. [30] Cementoblastic differentiation of human dental stem cells, a key cellular mechanism concerning periodontal regeneration, was reported to be stimulated by hypoxia in a HIF-1dependent manner. [31] The mechanisms underlying the role of HIF-1 and periodontal defense/pathogenesis, however, remain elusive.…”
Section: Co-relation With Cytokinesmentioning
confidence: 99%
“…It was suggested that HIF, HIF mimicking agents, or HIF stabilizing agents were considered triggers for the initiation and promotion of angiogenic-osteogenic coupling [100,101]. A recent animal study reported new bone and vessels formation induced by the overexpression of HIF-1α via adenovirus, leading to enhanced alveolar bone defect regeneration [102]. A similar result was reported from a study investigating bone loss arrest in ovariectomized C57BL/6 J mice via activated HIF-1α and Wnt/β-catenin signaling pathways [103].…”
Section: Hif and Bone Homeostasismentioning
confidence: 99%